Cult as the catalyst for division : cult disputes as the motive for schism in the pre-70 pluralistic environment - Heger, Paul, 1924- (Studies on the texts of the Desert of Judah, 2007)
The study asserts that conflicting sacrificial rules were the motive of the schism in Judean society, in the last period of the Second Temple. The study substantiates the thesis by a meticulous examination and comparison of the rabbinic and Qumran exegetical methods, and an exhaustive scrutiny of biblical sacrificial rules, demonstrating their deficiencies, the cause of the exegetical dissensions among the different groups. A short record of historical struggles, due to cult issues, and a scrutiny of Qumran literature, corroborating the utmost significance of the Temple cult in that group, complement the study. The study is useful for a comprehension of Qumran literature and particularly of the system of thought of its authors and their approach to the biblical writings.